The Dominant Factors of Employee Turnover Case Study: ABC Hotel - Ameliya, Rena; Febriansyah, Hary (Journal of Business and Management, 2017)
Abstract.The hospitality industry is one of industry that focuses on the quality of human resource. In order to provide the good service, the hospitality industry needs qualified human resources. This is because the hospitality industry fully oriented to customer’s satisfaction. The success of the hospitality industry can be seen from customer’s satisfaction through the services provided by the hotel. However, there is one problems faced by hospitality, there is the employee turnover. One of the hotels who experienced the employee turnover is ABC Hotel. The impact that felt because of the employee turnover are disrupting the operational of the hotel and also causing losses for the cost, time and a decrease in production and services. The questions and the purpose of this research is to determine the significant factors of the employee turnover at ABC Hotel. Referring to the concept of Santhanam et.al (2015). There are six factors about the employee turnover in hospitality industry. Those are recruitment, selection, training, performance appraisal, career growth opportunities, and salary & benefit. After determining the significant factors of the employee turnover at ABC Hotel, the purpose of this research is to reduce employee turnover at ABC Hotel. The researcher distributed the questionnaire to all employees of ABC Hotel and obtained 64 respondents. The results of the questionnaire collecting were processed by using binary logistic regression as a tool of data processing and analysis. From the research, the result that obtained are the significant factors of the employee turnover at ABC Hotel, the factors are recruitment and selection. Keywords: Employee Turnover, Recruitment, Selection, Training, Performance Appraisal, Career Growth Opportunities and Pay & Benefit